Subsídios para o planejamento de cursos de português como língua de acolhimento para imigrantes deslocados forçados no Brasil - Ana Paula de Araújo Lopez (2016)
Affiliated with the epistemological position of Indisciplinary Applied Linguistics (MOITA LOPES, 2006), this study presents the results of a research that proposed guidelines designed to work as a subsidy for planning courses of Portuguese as a Welcoming Language (AMADO, 2013; CABETE, 2010; GROSSO, 2010; LOPEZ & DINIZ, 2016, no prelo; SÃO BERNARDO, 2016) for forced displaced immigrants in Brazil. In the international context, where there are over 65 million forcibly displaced people (UNHCR, 2016) victims of different processes of Forced or Crisis Migration (AYDOS, 2010; CLOCHARD, 2007), Brazil stands out as a country signatory of the most relevant international treaties concerning these migrants, and also as a receiver of a growing number of forcibly displaced people (CONARE, 2016; MJC, 2016). Based on the premise that the Portuguese has an essential role in the process of appropriation of the territory (material and symbolically) by these immigrants the process of (re)territorialization (BIZON, 2013) , this work seeks to contribute for the formulation of courses of Portuguese as a Welcoming Language, aiming at the strengthening of this field of study. The adopted methodology was qualitative (SOUZA, 2014), with an ethnographic and interpretive perspective (BIZON, 2013), with a corpus comprehending participant observation in the context of teaching and learning Portuguese as a Welcoming Language, as well as the application of questionnaires for two groups of interest: the first composed by coordinators, teachers, and students from both the course offered by Centro Zanmi, and the course of Portuguese as a Foreign Language for Immigrants with Special Residence Status, offered by the Center of Language Outreach Programs at UFMG; while the second group was composed by coordinators and teachers of other similar initiatives in the country. The results point out to a tendency of the professionals of the area for a totalization (MAHER, 2007) of the forced displaced immigrants, identifying them mainly by their losses and faults, contributing to the construction of a helpless image of these immigrants (AYDOS, 2010). Additionally, we found out that a great number of immigrants understands the knowledge of Portuguese as a need or a self-defense tool, which can indicate that their processes of (re)territorialization (BIZON, 2013) are often held precariously. Finally, we point out that some challenges in planning courses of Portuguese as a Welcoming Language involve: the lack of specialized teaching materials, precariousness in teacher training, lack of student attendance, and flexibilization of the workload. Thus, the data indicate that the practice of Portuguese as a Welcoming Language has particularities that distinguish it from a simple adaptation of priori knowledge. Therefore, we suggest that these courses are planned within the perspective of the Interculturalism (MAHER, 2007), and involve two dimensions of action: the political strengthening of the forcibly displaced immigrants and the surrounding education, in order to foster worthy and more socially just processes of (re)territorialization (BIZON, 2013) for this population.